Pengaruh Brand Image, Product Quality, and Lifestyle Terhadap Purchase Decision Pada Richeese Factory - Prabowo, Gilang; Huda, Nurul (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
The purpose of this study is to determine the partial and simultaneous influence of brand image, product quality, and lifestyle on purchase decision at Richeese Factory. This research is quantitative in nature. The data sources used in this study are both primary and secondary data. The population in this study consists of the people of Jepara who have purchased food or beverages at Richeese Factory, with the exact number of the population being unknown. The sample in this study was determined using purposive sampling. Based on the unspecified population, the sample size was calculated using the Rao Purba formula, resulting in 96 respondents. The data collection technique used a questionnaire with a Likert scale ranging from 1 to 5. The data analysis technique applied in this study is multiple linear regression analysis, using SPSS version 26 as the analytical tool. Based on the results of the study, the first hypothesis shows that the brand image variable has a significant effect on purchase decision. The second hypothesis indicates that the product quality variable also has a significant effect on purchase decision. The third hypothesis reveals that the lifestyle variable has a significant effect on purchase decision. The fourth hypothesis shows that brand image, product quality, and lifestyle variables have a positive and significant effect on purchase decision.